Komunikasi Politik pada PPS di Desa Gedangsewu dalam Mensosialisasikan Pemilu 2024 - Retpitasari, Ellyda; Khoiriyah, Binti (Hikmah, 2023)
In order to welcome the 2024 elections, higher public participation, changes in political dynamics, and challenges in modern elections will be important points that need attention. These elections have the potential to bring about substantial changes in the political system, but also require a concerted effort from governments, political parties, and civil society to ensure the integrity, transparency, and inclusiveness of such elections. This requires important roles of the community in their respective domiciles. The most strategic level in socializing elections is the village. Inside there is a Voting Election Officer (PPS) whose job is to coordinate village communities to participate in the 2024 elections. Political communication is very influential in political strategy. In this study, researchers want to analyze how PPS socializes this upcoming election. The aim of this research is to ascertain the mechanism of political correspondence and its effects on the inhabitants of Gedangsewu Village. Employing Carl L. Hoylan's concept of mindset alteration, the mode of inquiry or information gathering adopted in this investigation is through documentation and conducting interviews.